Psychosocial functioning of young children with learning problems. - Gadeyne E; Ghesquière P; Onghena P (Journal of Child Psychology & Psychiatry, 2004)
BACKGROUND: In this study, psychosocial functioning of different groups of young children with learning problems was investigated using a diverse set of psychosocial variables (including behaviour problems, academic motivation, social preference, and self-concept). METHODS: For this purpose, children with low academic achievement, with a specific learning disability based on an IQ-achievement discrepancy, and with a specific learning disability based on an achievement discrepancy, were selected out of 276 children of the first grade of regular primary schools. By means of multivariate analyses, their psychosocial functioning was compared to the functioning of children without learning problems. RESULTS: The total set of psychosocial variables was able to discriminate between children with and without learning problems, with medium effect size. Attention problems as reported by the teachers turned out to be the most important single psychosocial predictor for group discrimination. However, results varied according to the type of learning problem and the type of psychosocial problem. Children with a specific reading/spelling disability and children with low general academic achievement differed most from their peers without learning problems with regard to their psychosocial functioning. Poor cognitive self-concept was related primarily to low academic achievement, poor learning motivation might be specific for math problems, and a low social preference score seemed most characteristic of children with a specific learning disability. CONCLUSIONS: Studying several psychosocial variables simultaneously in different groups of children with learning problems leads to a further refinement of the current knowledge.